2017
DOI: 10.1016/j.pmedr.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of subjective and objective measures of office workers' sedentary time

Abstract: Sedentary behavior is an independent and prominent risk factor for chronic disease. Occupational sitting is likely to be the largest determinant of overall daily sitting time. Gathering accurate data on sedentary behaviors is essential to determine prevalence and effectiveness of interventions to reduce sedentary time. The purpose of this research was to determine whether self-reported sedentary time assessed by the Paffenbarger Physical Activity Questionnaire (PPAQ) and the Occupational Sitting and Physical A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 40 publications
(64 reference statements)
1
28
0
Order By: Relevance
“…However, MR studies are less likely to be affected by measurement error on the exposures than conventional observational analyses 39 . The data used to obtain information about sedentary behaviours were subjectively measured, which are known to underestimate the actual sedentary time 40 , any possible measurement errors are likely biased towards the null. In addition, since the questionnaire did not include occupational sedentary behaviours, conclusions cannot be generalized to total sedentary behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…However, MR studies are less likely to be affected by measurement error on the exposures than conventional observational analyses 39 . The data used to obtain information about sedentary behaviours were subjectively measured, which are known to underestimate the actual sedentary time 40 , any possible measurement errors are likely biased towards the null. In addition, since the questionnaire did not include occupational sedentary behaviours, conclusions cannot be generalized to total sedentary behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…1,27 Except for South Africa and India (2 medium HDI countries with some accelerometer data), the other 7 countries relied on subjective data and/or expert opinions to evaluate overall physical activity. Such reliance on subjective data, which are known to be prone to recall and other biases, 57 may impact the accuracy of the reported results. Furthermore, over one-third of the indicators could not be assigned grades due to the unavailability or insufficiency of relevant data.…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies examined and compared the criterion validity of self-report measures under the following conditions: nine studies (19 comparisons) on weekday/ workday (includes time at work and outside of work) vs. weekend/non-workday sedentary time [24,47,51,58,69,70,86,156,198]; 2 studies (5 comparisons) on minutes per day of self-reported television time [141,155]; nine studies (11 comparisons) on minutes per day of occupational sedentary time [61,65,75,99,101,105,122,136,181,188,193]; and, four studies (five comparisons) on the proportion of a workday spent sedentary [91,105,158,205]. In all of these studies a comparable criterion was required (e.g., self-reported occupational sitting was compared to accelerometer sedentary time during work time only).…”
Section: Validitymentioning
confidence: 99%